Online hate speech and emotions on Twitter: a case study of Greta Thunberg at the UN Climate Change Conference COP25 in 2019 - Arce García, Sergio; Díaz-Campo, Jesús; Cambronero Saiz, Belén (Social Network Analysis and Mining, 2023)
The presence of environmental activist Greta Thunberg at the UN Climate Change Conference COP25 in 2019 prompted reactions on social media, which grew exponentially after she was named Time Magazine's Person of the Year 2019 and even more so after then-president of the United States Donald Trump tweeted his reaction to her accolade. An analysis of 1,395,054 tweets gathered between November and December 2019 through R, network theory techniques, machine learning and natural language processing showed how messages sparking hatred and intense emotions generate posts, mainly negative ones that subsequently serve as catalysts. The results also demonstrate the relevance of the bubble filter and echo chamber theories and the fact that hate springs from a range of sentiments depending on each participant group.
Keywords: climate summit; Greta Thunberg; hate; machine learning; sentiment; social media; Scopus; Emerging